2016
DOI: 10.1111/efp.12299
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Phytophthora alni complex and P. plurivora in Alnus glutinosa seedlings

Abstract: Summary The ecological importance of riparian forests is well known. However, these forest habitats have been disturbed by human activities over the past century as a result of the introduction of flow regulations. Mortality of the riparian alder population caused by Phytophthora has become an important issue in Europe in the past two decades. The main objective of this study was to examine the pathogenicity of the Phytophthora alni complex (P. xalni, P. uniformis and P. xmultiformis) and P. plurivora in Alnus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…plurivora from clade 2 is known to be a serious pathogen of many forest trees, including oak, beech, and Alnus glutinosa seedlings. This species can cause dieback and root loss and is most frequently associated with cankers in Europe, North America, and Asia [31][32][33][50][51][52][53][54][55]. Via the examination of plant tissues and soil samples, it has been reported to cause cankers in wild apple forests in Xinjiang [17], corroborating its discovery in stream water and soil samples in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…plurivora from clade 2 is known to be a serious pathogen of many forest trees, including oak, beech, and Alnus glutinosa seedlings. This species can cause dieback and root loss and is most frequently associated with cankers in Europe, North America, and Asia [31][32][33][50][51][52][53][54][55]. Via the examination of plant tissues and soil samples, it has been reported to cause cankers in wild apple forests in Xinjiang [17], corroborating its discovery in stream water and soil samples in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…), highly susceptible to the oomycete Phytophthora ×alni Brasier & S. A. Kirk; and (3) U. minor , highly susceptible to the ascomycete Ophiostoma novo‐ulmi Brasier. These three pathosystems were selected as they are widespread and have resulted in extensive dieback and tree mortality in southern Europe (Alcaide et al., 2020; Ghelardini et al., 2017; Jung et al., 2018; Solla et al., 2010; Zamora‐Ballesteros et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have demonstrated that other Phytophthora species are involved in the aetiology of alder decline. In particular, the plurivorous pathogen P. plurivora has recurrently been isolated from declining alders in different countries [13][14][15] and its pathogenicity towards alders has been demonstrated [15,16].…”
Section: Introductionmentioning
confidence: 99%